Do deaf individuals have better visual skills in the periphery? Evidence from processing facial attributes. Issue 3 (15th March 2020) - Shalev, Tal; Schwartz, Sivan; Miller, Paul; Hadad, Bat-Sheva
ABSTRACT: Studies examining visual abilities in individuals with early auditory deprivation have reached mixed conclusions, with some finding congenital auditory deprivation and/or lifelong use of a visuospatial language improves specific visual skills and others failing to find substantial differences. A more consistent finding is enhanced peripheral vision and an increased ability to efficiently distribute attention to the visual periphery following auditory deprivation. However, the extent to which this applies to visual skills in general or to certain conspicuous stimuli, such as faces, in particular is unknown. We examined the perceptual resolution of peripheral vision in the deaf, testing various facial attributes typically associated with high-resolution scrutiny of foveal information processing. We compared performance in face-identification tasks to performance using non-face control stimuli. Although we found no enhanced perceptual representations in face identification, gender categorization, or eye gaze direction recognition tasks, fearful expressions showed greater resilience than happy or neutral ones to increasing eccentricities. In the absence of an alerting sound, the visual system of auditory deprived individuals may develop greater sensitivity to specific conspicuous stimuli as a compensatory mechanism. The results also suggest neural reorganization in the deaf in their opposite advantage of the right visual field in face identification tasks.